Gallstones in the young: Epidemiological review - Aizen Tub, Bernardo; Beltrán Guañarita, Jorge; Gómez Fossati, Carlos (Cirugía del Uruguay, 1991)
series of 172 young patients suffering from biliar lithiasis is presented. lts epidemiological revision is made, as regards incidence, predisposing factors, clinical presentations, and therapeutics. Taking results into account, considerations are made on surgica/ opportunity